1995
DOI: 10.1097/00002371-199505000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Defective Major Histocompatibility Complex Class I Expression in a Sarcomatoid Renal Cell Carcinoma Cell Line

Abstract: SummaryWe studied major histocompatibility complex (MHC) class I expression in 12 tumor cell culture lines established from patients with metastatic renal cell carcinoma (RCC). In one of these cell culture lines, UOK 123, we found no surface expression of β 2 -microglobulin (β 2 m) and MHC class I by flow cytometry. Immunofluorescence staining using three different monoclonal antibodies to β 2 m revealed no detectable β 2 m in the endoplasmic reticulum (ER), Golgi apparatus, cytoplasm, or on the cell surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Therefore, we are fully aware of the limitation in drawing a definitive conclusion concerning the frequency of specific defect(s) for a given RCC type before more tumor lesions and cell lines are investigated. The total HLA class I loss identified here in the sarcomatoid RCC subtype is in line with a previous study in which another sarcomatoid RCC cell line known as UOK123 was found to have lost total HLA class I expression; however, no information was given regarding its underlying mechanism [11]. Therefore, given the notorious clinical feature of sarcomatoid RCC, our study may have provided useful pilot data regarding the molecular defects in this subtype that lead to a total HLA class I loss.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we are fully aware of the limitation in drawing a definitive conclusion concerning the frequency of specific defect(s) for a given RCC type before more tumor lesions and cell lines are investigated. The total HLA class I loss identified here in the sarcomatoid RCC subtype is in line with a previous study in which another sarcomatoid RCC cell line known as UOK123 was found to have lost total HLA class I expression; however, no information was given regarding its underlying mechanism [11]. Therefore, given the notorious clinical feature of sarcomatoid RCC, our study may have provided useful pilot data regarding the molecular defects in this subtype that lead to a total HLA class I loss.…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, tumour cells may have developed mechanisms that allow immune escape. Those mechanisms proposed include suppression mediated by cytokines released by tumour cells, 17 and reduced expression of MHC and costimulatory molecules on tumour cells 18 , 19 . More recent evidence suggests that expression of the apoptotic death factor molecule, Fas (APO‐1/CD95) ligand (Fas L), on tumour cells may represent a novel mechanism of immune evasion 20 , 21 , 22 , 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In an assessment of 12 RCC patient-derived cell lines, Jakobsen et al identified a lack of both β 2 -microglobulin expression and major histocompatibility complex (MHC) class I expression in a cell line derived from a patient with sarcomatoid disease. [16] Notably, β 2 -microglobulin allows for appropriate folding of MHC class I complex on the cell surface – the lack of this complex precludes antigen presentation and allows for immune invasion. In a separate effort, Kuriowa et al performed a detailed immunohistochemical analysis of 12 specimens derived from patients with sarcomatoid RCC.…”
Section: Discussionmentioning
confidence: 99%